Determination of HMF, glucose and fructose contents in various honey samples - Řezková, Soňa; Adam, Martin; Královský, Josef; Kahoun, David; Červenka, Libor (Univerzita Pardubice, 2008)
The paper deals with estimation of the concentration changes of 5-hydroxymethyl-2-furfuraldehyde (HMF), fructose and glucose in various honey samples after their heating. The content of HMF in honey was analysed by liquid chromatography (HPLC) method coupled with ultraviolet (UV) detection. The content of glucose and fructose in honey was analysed by HPLC method using evaporative light scattering detection (ELSD). Chromatographic conditions were optimized for HMF, fructose and glucose analyses. The obtained limits of detection (LOD) in honey were 0.25 mg kg-1 for HMF, 0.18 g kg-1 for fructose and 0.26 g kg-1 for glucose. Samples of honey were exposed to the temperatures of 50, 60, 70, and 80 °C and the concentrations of target analytes were monitored. The highest increase in HMF was found in liquid honey heated up to 80 °C and the concentrations of target analytes were monitored. The highest increase in HMF was found in liquid honey heated up to 80 °C, where the acceptable limit (40 mg kg-1 HMF in honey by EU) was exceeded after 5 hours of heating. The creamed honey did not exceed the limit of HMF even after 8 hours. The amount of HMF was significantly higher in honey samples purchased from retailers compared to samples purchased from beekeepers.